L1-based strategies in learning the grammar of L2 English and L3 Russian by Polish learners. (October 2016) - Wach, Aleksandra
Abstract: The study examined the use of the L1 (Polish) as a strategy in learning the grammar of L2 English and L3 Russian by trilingual learners. The participants were 85 university students who were upper-intermediate learners of English and beginner/elementary learners of Russian, and the research data were elicited via a questionnaire and a follow-up interview with nine of the participants. The results revealed that the L1 was an important resource in learning L2 and L3 grammar, especially in the case of L3 Russian. Significant differences between the frequency and patterns of L1-based strategy use in learning the grammar of both languages were found, which can be explained by the L2 and L3 proficiency levels and language psychotypology. It can be concluded that the reported differentiation in strategy use with regard to the language-related (typology) and learner-related (proficiency) factors points to high levels of metacognitive and cross-linguistic awareness of the research sample.